An anti-caking tablet for metallocene olefin polymerization process

By using anti-table tablets containing alkane oil solvent, fatty acid compounds, fatty acid salt compounds and emulsifiers in the metallocene olefin polymerization process, the existing anti-table tablets are solved inactivation and dispersion stability in the metallocene catalyst system. The poor performance problem has achieved the effect of effectively preventing patches and expanding the application range.

CN118702849BActive Publication Date: 2025-02-14PETROCHINA SHANGHAI ADVANCED MATERIALS RESEARCH INSTITUTE CO LTD +1

Patent Information

Application Number
CN202411203514.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-02-14
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

The existing anti-catalyst tablets are prone to deactivation of the catalyst in the metallocene catalyst system, poor dispersion stability, and limited in food contact use, making it difficult to effectively prevent the tableting phenomenon in the olefin polymerization reactor.

Method used

Develop an anti-caking tablet for metallocene olefin polymerization process, containing alkane oil solvent, fatty acid compounds, fatty acid salt compounds and emulsifiers, and improve the dispersion of anti-caking tablets through the ratio and combination of these components. Stability and ensure no significant impact on the activity of metallocene catalysts.

Benefits of technology

It effectively reduces the agglomerated tablet problem during the polymerization of metallocene olefins, improves the dispersion stability of anti-caking tablets, ensures that the catalyst activity is not affected, and expands the application range of products, including food contact uses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118702849B_ABST
    Figure CN118702849B_ABST
Patent Text Reader

Abstract

The present invention relates to an anti-caking tablet for metallocene olefin polymerization process, wherein the anti-caking tablet comprises the following raw material components in parts by weight: 50-99.9 parts of alkane oil solvent, 0.01-20 parts of fatty acid compounds, 0.01-40 parts of fatty acid salt compounds, and 0.001-5 parts of emulsifiers. Compared with the prior art, the present invention can effectively prevent, reduce or stop the agglomeration and flake problem of polyolefin particles during the polymerization process, improve the dispersion stability of the anti-caking tablet, and have no obvious adverse effect on the activity of the matching metallocene catalyst. At the same time, the obtained final product can be used for various applications such as food contact.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of additives for olefin polymerization processes, and relates to an anti-caking tablet for metallocene olefin polymerization processes. Background Art

[0002] Polyolefin resins are a type of new polymer material with a wide range of applications, and they occupy an important strategic position in the chemical industry chain. Polyethylene and polypropylene are the two polyolefin resins with the largest output. The traditional olefin polymerization process has the characteristics of strong heat release, and polyolefin particles are prone to agglomeration in the reactor, which causes adhesion to the wall and produces flakes, affecting the heat and mass transfer inside the reactor. Especially for the metallocene catalyst system, its high reaction activity and fast initial reaction rate cause the local reaction temperature to rise sharply, which is more likely to cause flakes in the reactor.

[0003] It is generally believed that there are three main forms of flakes in olefin polymerization reactors, namely "hot flakes", "cold flakes" and "bonding flakes". "Hot flakes" are caused by the excessive activity of the catalyst, which makes it difficult to remove the heat of reaction in time, causing the polyolefin particles to melt and form flakes. "Cold flakes" are caused by the small particle size and large surface free energy of polyolefin powder particles, which have a natural tendency to self-agglomerate, thus agglomerating and forming flakes. "Bonding flakes" are the result of the interaction between "hot flakes" and "cold flakes". The "bonding flakes" are centered on the molten polyolefin, with filamentous polymers extending from the edges and covered with polyolefin powder particles.

[0004] The flake formation in the reactor will increase the flakes or blocks, causing blockage in the reactor pipeline, and even cause explosion and shutdown in severe cases. It hinders the long-term operation of the device, inhibits the release of the device's production capacity, increases the operating cost of the device, and significantly reduces the performance and quality of the polymer products. Abnormal flake formation in the reactor has become a major technical problem that plagues the long-term operation of olefin polymerization units.

[0005] At present, the flake problem in olefin polymerization reactors can be controlled through a variety of ways, including treating the reactor surface, changing operating conditions, innovating reactor design, using anti-caking tablets, etc. For example, U.S. Patent No. 4956427A discloses a method for coating the surface of a polymerization reactor, U.S. Patent No. 3984387A discloses a method for synchronously injecting an inert gas into a reactor, European Patent No. 2966094B1 discloses a new reactor design to avoid flakes, and U.S. Patent No. 9303095B2 discloses the use of an additive containing alkylbenzene sulfonic acid to control flakes. Injecting anti-caking tablets is the most widely used and most effective prevention and control measure in actual production, but because metallocene catalysts are very sensitive to impurities, traditional anti-caking tablets can easily cause metallocene catalysts to deactivate and reduce the performance of polyolefin products. At the same time, the dispersion stability of anti-caking tablets has important guiding significance for their industrial application. Traditional anti-caking tablets often experience sedimentation and stratification when used on site, which greatly reduces the actual effect of anti-caking tablets. In addition, the use of additives such as anti-caking tablets in the preparation of polyolefin products for food contact is often limited by regulations such as those of the European Commission and the US Food and Drug Administration, which have restrictions on compounds including ethoxylated amines, alkylbenzene sulfonic acids, random ethylene oxide / propylene oxide copolymers, etc.

[0006] In view of the problems of conventional anti-caking tablets such as catalyst deactivation, poor dispersion stability, limited food application and poor anti-caking effect, it is urgent to develop anti-caking tablets suitable for the metallocene catalyst olefin polymerization process to meet the actual needs of the development of the polyolefin industry. Summary of the invention

[0007] The purpose of the present invention is to provide an anti-caking tablet for metallocene olefin polymerization process and its preparation and application, so as to prevent, reduce or stop the agglomeration and flake problem of polyolefin particles during the polymerization process, improve the dispersion stability of the anti-caking tablet, and have no obvious adverse effect on the activity of the matching metallocene catalyst. At the same time, the final product obtained can be used for various applications such as food contact purposes.

[0008] The purpose of the present invention can be achieved by the following technical solutions:

[0009] In a first aspect, the present invention provides an anti-caking tablet for metallocene olefin polymerization process, comprising the following raw material components in parts by weight: 50 to 99.9 parts of alkane oil solvent, 0.01 to 20 parts of fatty acid compounds, 0.01 to 40 parts of fatty acid salt compounds, and 0.001 to 5 parts of emulsifier.

[0010] Furthermore, the anti-caking tablet may be in a solid, gel or fluid form. When the anti-caking tablet is in a fluid form, it may be in a pure liquid form, a solid suspension form, a slurry form or a combination thereof.

[0011] Furthermore, the fatty acid compound and / or fatty acid salt compound may be in the form of particles or partially swollen or partially dissolved or completely dissolved in the alkane oil solvent. When the fatty acid compound and / or fatty acid salt compound is in the form of particles or partially swollen or partially dissolved in the alkane oil, it may be in the form of floating, suspension, sedimentation, sinking, stratification, emulsification and other dispersion forms.

[0012] Furthermore, the anti-caking tablet comprises the following raw material components in parts by weight: 75-95 parts of alkane oil solvent, 0.1-5 parts of fatty acid compounds, 5-30 parts of fatty acid salt compounds, and 0.001-1 part of emulsifier.

[0013] Further, the alkane oil solvent includes one or a combination of pentane, hexane, heptane, toluene, xylene, cyclohexane, petroleum ether, white oil, mineral oil, base oil, and liquid paraffin, preferably one or more of white oil, mineral oil, base oil, and liquid paraffin. More specifically, white oil, mineral oil, base oil, and liquid paraffin include various types of different grades, different viscosities, different boiling ranges, and different molecular weights.

[0014] Furthermore, the fatty acid compound includes one or a mixture of palmitoleic acid, oleic acid, ricinoleic acid, linoleic acid, linolenic acid, arachidonic acid, hexadecanoic acid or octadecanoic acid.

[0015] Further, the fatty acid salt compound includes a mono-fatty acid aluminum compound, a di-fatty acid aluminum compound, a tri-fatty acid aluminum compound or a combination thereof. Specifically, the fatty acid salt compound is one or more of mono-stearate aluminum, distearate aluminum or tri-stearate aluminum.

[0016] The "emulsifier" of the present invention should be broadly defined as an agent or agent combination that can improve the dispersion stability of fatty acid compounds and / or fatty acid salt compounds in an alkane oil solvent.

[0017] Further, the emulsifier includes one or a combination of glyceryl monostearate, fatty amine salts, alkyl sulfates, alkylbenzene sulfonates, phosphates, N-dodecyl dimethylamine, quaternary ammonium salts, fatty acid soaps, polyoxyethylene ethers, polyoxypropylene ethers, ethylene oxide and propylene oxide block copolymers, polyol fatty acid esters, polyvinyl alcohol, Tween, span, glycerol fatty acid esters. Exemplarily, the emulsifier can be sodium lauryl sulfate.

[0018] In a second aspect, the present invention provides a method for preparing anti-caking tablets for metallocene olefin polymerization process, wherein an alkane oil solvent, a fatty acid compound, a fatty acid salt compound, and an emulsifier are weighed according to a ratio, and stirred to mix thoroughly to obtain anti-caking tablets.

[0019] In a third aspect, the present invention provides an application of an anti-caking tablet for a metallocene olefin polymerization process in olefin polymerization.

[0020] Furthermore, the olefin polymerization method includes a solution method, a gas phase method, a slurry method, or a high pressure method. Exemplarily, the olefin polymerization adopts a slurry method.

[0021] Further, olefin polymerization includes ethylene polymerization, propylene polymerization, butene polymerization, pentene polymerization, hexene polymerization, octene polymerization, α-olefin polymerization, or cycloolefin polymerization. Exemplarily, olefin polymerization is ethylene polymerization.

[0022] Furthermore, during olefin polymerization, the amount of the anti-caking tablet added is 0.01 to 10000 ppm of the mass of the slurry solvent or the mass of the polyolefin product in the polymerization reaction.

[0023] Compared with the prior art, the present invention has the following advantages:

[0024] (1) The anti-agglomeration tablets of the present invention can not only effectively reduce the agglomeration problem in the metallocene olefin polymerization process, but also have no significant effect on the activity of the supporting metallocene catalyst;

[0025] (2) The present invention introduces fatty acid compounds, fatty acid salt compounds and emulsifiers into alkane oil, which effectively improves the dispersion stability of anti-caking tablets;

[0026] (3) The alkane oil solvent, fatty acid compound and fatty acid salt compound used in the present invention are widely used in the polyolefin production process, have no obvious biological toxicity, and can expand the application range of polyolefin products. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 A photograph of polyolefin particles showing unagglomerated flakes;

[0028] Figure 2 Photograph of polyolefin particles showing agglomerated flakes. DETAILED DESCRIPTION

[0029] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0030] The metallocene catalysts in the following examples can be purchased from a variety of sources, such as the metallocene catalyst sold under the trade name AC-101 by WR Grace & Co. and the metallocene catalyst sold under the trade name TH-5 by Zibo Xinjuku Chemical Co., Ltd.

[0031] Although two commercial metallocene catalysts are disclosed in the examples of the present invention, the protection scope of the present invention should not be limited thereto. Relevant personnel in the technical field may replace and use other metallocene catalysts or metallocene catalyst combinations.

[0032] The compounds, compositions, ingredients, mixtures, preparation methods, dispersion forms and apparent properties disclosed in the present invention, unless otherwise specified, should be understood that the present invention is not limited to specific compounds, compositions, ingredients, mixtures, preparation methods, dispersion forms, apparent properties and temperature, pressure, metallocene catalysts, etc., because the above conditions can be adjusted according to circumstances. The terms used in the present invention are only for the purpose of being more suitable for describing the embodiments, and are not therefore used as limiting conditions for the protection of the present invention.

[0033] The formula components of the anti-caking tablets in the embodiments provided by the present invention mainly include four types of components: the first type of component is an alkane oil solvent, code-named "component A", taking mineral oil as an example, purchased from Sinopharm Wokai Company, with a specification of 25 cSt at 40°C; the second type of component is a fatty acid compound, code-named "component B", taking stearic acid as an example; the third type of component is a fatty acid salt compound, code-named "component C", and the fourth type of component is an emulsifier, taking sodium dodecyl sulfate as an example, purchased from McLean Company. Among them, the third type of component fatty acid salt compounds can be further preferably subdivided, including monofatty acid aluminum compounds, taking aluminum monostearate as an example, code-named "component C1"; difatty acid aluminum compounds, taking aluminum distearate as an example, code-named "component C2"; trifatty acid aluminum compounds, taking aluminum tristearate as an example, code-named "component C3".

[0034] Comparative Example 1

[0035] Weigh 75 g of component A and 25 g of component B into a sample bottle and mix thoroughly by mechanical stirring. After mixing, let it stand and no obvious sedimentation or stratification occurs within 7 days.

[0036] Comparative Example 2

[0037] Weigh 75 g of component A and 25 g of component C1 into a sample bottle and mix thoroughly by mechanical stirring. After mixing, let it stand for 6 days without obvious sedimentation and stratification, but after 7 days, obvious sedimentation and stratification will appear.

[0038] Comparative Example 3

[0039] Weigh 75 g of component A and 25 g of component C2 into a sample bottle and mix thoroughly by mechanical stirring. After mixing, let it stand for 5 days without obvious sedimentation and stratification, but after 6 days, obvious sedimentation and stratification will appear.

[0040] Comparative Example 4

[0041] Weigh 75 g of component A and 25 g of component C3 into a sample bottle and mix thoroughly by mechanical stirring. After mixing, let it stand for 4 days without obvious sedimentation and stratification, but after 5 days, obvious sedimentation and stratification appeared.

[0042] Comparative Example 5

[0043] Weigh 80 g of component A and 20 g of component C3 into a sample bottle and mix them thoroughly by mechanical stirring. After mixing, let it stand for 4 days without obvious sedimentation and stratification, but after 5 days, obvious sedimentation and stratification appeared.

[0044] Comparative Example 6

[0045] Weigh 85 g of component A and 15 g of component C3 into a sample bottle and mix thoroughly by mechanical stirring. After mixing, let it stand for 3 days without obvious sedimentation and stratification, but after 4 days, obvious sedimentation and stratification appeared.

[0046] Comparative Example 7

[0047] Weigh 90 g of component A and 10 g of component C3 into a sample bottle and mix thoroughly by mechanical stirring. After mixing, let it stand for 2 days without obvious sedimentation and stratification, but after 3 days, obvious sedimentation and stratification will appear.

[0048] Comparative Example 8

[0049] Weigh 95 g of component A and 5 g of component C3 into a sample bottle and mix thoroughly by mechanical stirring. After mixing, let it stand for 1 day without obvious sedimentation and stratification, but after 2 days, obvious sedimentation and stratification will appear.

[0050] Comparative Example 9

[0051] Weigh 75 g of component A, 5 g of component B and 20 g of component C3 into a sample bottle and mix them thoroughly by mechanical stirring. After mixing, let it stand for 6 days without obvious sedimentation and stratification, but after 7 days, obvious sedimentation and stratification will appear.

[0052] Comparative Example 10

[0053] Weigh 75 g of component A, 25 g of component C3 and 0.1 g of emulsifier into a sample bottle and mix thoroughly by mechanical stirring. After mixing, let it stand and no obvious sedimentation or stratification occurs within 7 days.

[0054] Example 1

[0055] Weigh 75 g of component A, 4.9 g of component B, 20 g of component C3 and 0.1 g of emulsifier into a sample bottle and mix thoroughly by mechanical stirring. After mixing, let it stand and no obvious sedimentation or stratification occurs within 7 days.

[0056] Table 1 below provides the formulation compositions of the anti-caking tablets of Comparative Examples 1 to 10 and Example 1.

[0057] Table 1

[0058]

[0059] The dispersion stability of the anti-caking tablet has important guiding significance for its practical application. In the examples of the present invention, it is specifically described whether the anti-caking tablet has obvious sedimentation and stratification within 7 days.

[0060] Table 2 below provides whether the anti-caking tablets of Comparative Examples 1 to 10 and Example 1 show obvious sedimentation and stratification within 7 days. In Table 2, "no obvious sedimentation and stratification" is marked as "√", and "obvious sedimentation and stratification" is marked as "×". As can be seen from Table 2, Example 1 containing component A, component B, component C3 and emulsifier did not show obvious sedimentation and stratification within 7 days. At the same time, Comparative Example 10 containing component A, component C3 and emulsifier also did not show obvious sedimentation and stratification within 7 days. Compared with Comparative Examples 1-9, Comparative Example 10 and Example 1 with the addition of emulsifier have slower sedimentation and stratification rates, indicating that the emulsifier can effectively improve the dispersion stability of anti-caking tablets.

[0061] Table 2

[0062]

[0063] Example 2

[0064] The anti-caking tablet formulation in Example 1 was used to carry out a slurry olefin polymerization test. 700 g of n-hexane, 5 g of triethylaluminum, 0.07 g of anti-caking tablet and 0.2 g of metallocene catalyst TH-5 were added to the slurry polymerization reactor. The stirring rate was 500 rpm, the pressure was 1 MPa, the temperature was 80 °C, the reaction time was 1 hour, and the ethylene feed was set to automatic adjustment. The test results showed that the activity of the catalyst was 883 gPE / gCat·h, and the activity unit was defined as the mass of the target product obtained per unit mass of catalyst per unit time. The residue of the polyolefin product on the 10-mesh sieve, such as Figure 1 The polyolefin product was polyolefin particles without obvious agglomeration or flakes, and very little residue remained on the 10-mesh sieve, indicating that no obvious flakes occurred in the reactor.

[0065] In addition, the following are references for determining whether obvious flaking occurs:

[0066] The polyolefin product residue on the 10-mesh sieve can be divided into two situations. One is that the polyolefin particles are larger in size, that is, each particle size is greater than 2000μm; the other is that many polyolefin particles are agglomerated together to form pieces with a size much larger than 2000μm, but after pressure is applied, the pieces will break apart and become multiple polyolefin particles with smaller particle sizes. Figure 1 and Figure 2 It can be intuitively seen whether large-sized flakes are formed by many polyolefin particles agglomerating together, that is, whether obvious flakes have occurred.

[0067] Example 3

[0068] The anti-caking tablet formulation in Example 1 was used for slurry olefin polymerization test. 700 g of n-hexane, 5 g of triethylaluminum, 0.035 g of anti-caking tablet and 0.2 g of metallocene catalyst AC-101 were added to the slurry polymerization reactor, the stirring rate was 500 rpm, the pressure was 1 MPa, the temperature was 80 °C, the reaction time was 1 hour, and the ethylene feed was set to automatic adjustment. The test results showed that the activity of the catalyst was 937 gPE / gCat·h. From the residual situation of the polyolefin product on the 10-mesh sieve, it can be seen that no obvious flake phenomenon occurred in the polymerization reactor.

[0069] Example 4

[0070] The anti-caking tablet formulation in Example 1 was used for slurry olefin polymerization test. 700 g of n-hexane, 5 g of triethylaluminum, 0.07 g of anti-caking tablet and 0.2 g of metallocene catalyst AC-101 were added to the slurry polymerization reactor, the stirring rate was 500 rpm, the pressure was 1 MPa, the temperature was 80 ° C, the reaction time was 1 hour, and the ethylene feed was set to automatic adjustment. The test results showed that the activity of the catalyst was 913 gPE / gCat·h. From the residual situation of the polyolefin product on the 10-mesh sieve, it can be seen that no obvious flake phenomenon occurred in the polymerization reactor.

[0071] Example 5

[0072] The anti-caking tablet formulation in Example 1 was used for slurry olefin polymerization test. 700 g of n-hexane, 5 g of triethylaluminum, 0.14 g of anti-caking tablet and 0.2 g of metallocene catalyst AC-101 were added to the slurry polymerization reactor, the stirring rate was 500 rpm, the pressure was 1 MPa, the temperature was 80 °C, the reaction time was 1 hour, and the ethylene feed was set to automatic adjustment. The test results showed that the activity of the catalyst was 919 gPE / gCat·h. From the residual situation of the polyolefin product on the 10-mesh sieve, it can be seen that no obvious flake phenomenon occurred in the polymerization reactor.

[0073] Comparative Example 11

[0074] No anti-caking tablets were added in the slurry olefin polymerization test. 700 g of n-hexane, 5 g of triethylaluminum and 0.2 g of metallocene catalyst AC-101 were added to the slurry polymerization reactor, the stirring rate was 500 rpm, the pressure was 1 MPa, the temperature was 80 °C, the reaction time was 1 hour, and the ethylene feed was set to automatic adjustment. The test results showed that the activity of the catalyst was 901 gPE / gCat·h. The residual condition of the polyolefin product on the 10-mesh sieve, such as Figure 2 , the polyolefin particles were obviously agglomerated and flaked, indicating that obvious flake formation occurred in the polymerization reactor.

[0075] Comparative Example 12

[0076] The anti-caking tablet formula in Comparative Example 10 was used for slurry olefin polymerization test. 700 g of n-hexane, 5 g of triethylaluminum, 0.035 g of anti-caking tablet and 0.2 g of metallocene catalyst AC-101 were added to the slurry polymerization reactor, the stirring rate was 500 rpm, the pressure was 1 MPa, the temperature was 80 ° C, the reaction time was 1 hour, and the ethylene feed was set to automatic adjustment. The test results showed that the activity of the catalyst was 935 gPE / gCat·h. The residual situation of the polyolefin product on the 10-mesh sieve showed that the polyolefin particles with obvious agglomeration and flakes occurred, indicating that obvious flakes occurred in the polymerization reactor.

[0077] Comparative Example 13

[0078] The anti-caking tablet formula prepared by component A, component B and emulsifier in the ratio of 75:24.9:0.1 was selected for slurry olefin polymerization test. 700 g of n-hexane, 5 g of triethylaluminum, 0.035 g of anti-caking tablet and 0.2 g of metallocene catalyst AC-101 were added to the slurry polymerization reactor, the stirring rate was 500 rpm, the pressure was 1 MPa, the temperature was 80 ℃, the reaction time was 1 hour, and the ethylene feed was set to automatic adjustment. The test results showed that the activity of the catalyst was 243 gPE / gCat·h. The catalyst activity results show that the anti-caking tablet formula will have a significant effect on the activity of the matching metallocene catalyst.

[0079] Comparative Example 14:

[0080] The anti-caking tablet formula prepared by component A, component B, sodium oleate and emulsifier in the ratio of 75:4.9:20:0.1 was selected for slurry olefin polymerization test. 700 g of n-hexane, 5 g of triethylaluminum, 0.035 g of anti-caking tablet and 0.2 g of metallocene catalyst AC-101 were added to the slurry polymerization reactor, the stirring rate was 500 rpm, the pressure was 1 MPa, the temperature was 80 ℃, the reaction time was 1 hour, and the ethylene feed was set to automatic adjustment. The test results showed that the activity of the catalyst was 359gPE / gCat·h. The catalyst activity results show that the anti-caking tablet formula will have a significant effect on the activity of the matching metallocene catalyst.

[0081] It can be seen from the sedimentation and stratification of the above-mentioned embodiments that the anti-caking tablets of the present invention have good dispersion stability. It can be seen from the results of the metallocene catalyst activity in the above-mentioned embodiments and comparative examples that the anti-caking tablets of the present invention will not significantly affect the activity of the supporting metallocene catalyst. It can be seen from the results of the residual amount of polyolefin products on the 10-mesh sieve in the embodiments and comparative examples that the anti-caking tablets of the present invention can effectively reduce the agglomeration and flake problem in the metallocene olefin polymerization process.

[0082] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. An anti-caking tablet for metallocene olefin polymerization process, characterized in that: The method is composed of the following raw material components in parts by weight: 50-99.9 parts of alkane oil solvent, 0.1-5 parts of fatty acid compounds, 5-30 parts of fatty acid salt compounds, and 0.001-1 parts of emulsifier; The fatty acid salt compound is selected from aluminum monostearate, aluminum distearate, aluminum tristearate or a combination thereof; The alkane oil solvent is selected from one or a combination of pentane, hexane, heptane, toluene, xylene, cyclohexane, petroleum ether, white oil, and base oil; The fatty acid compound is one or a mixture of hexadecanoic acid or octadecanoic acid; The emulsifier is selected from one or a combination of glyceryl monostearate, fatty amine salts, alkyl sulfates, alkylbenzene sulfonates, phosphates, N-dodecyldimethylamine, quaternary ammonium salts, fatty acid soaps, polyoxyethylene ethers, polyoxypropylene ethers, ethylene oxide and propylene oxide block copolymers, polyol fatty acid esters, polyvinyl alcohol, Tween, span, and glycerol fatty acid esters.

2. Use of the anti-caking tablet for metallocene olefin polymerization process as claimed in claim 1 in olefin polymerization.

3. The use of the anti-caking tablet according to claim 2, characterized in that: The olefin polymerization method is solution method, gas phase method, slurry method or high pressure method; The olefin polymerization is ethylene polymerization, propylene polymerization, butene polymerization, pentene polymerization, hexene polymerization, octene polymerization or cycloolefin polymerization.

4. The use of the anti-caking tablet according to claim 2, characterized in that: During olefin polymerization, the amount of the anti-caking tablet added is 0.01 to 10000 ppm of the mass of the slurry solvent or the mass of the polyolefin product in the polymerization reaction.

Citation Information

Patent Citations

  • Olefin polymerization method

    EP2966094B1

  • Preparation of linear {60 -olefin polymers having ultra high molecular weight

    US3984387A

  • Process for reducing polymer build-up in polymerization equipment during polymerization of alpha-olefins

    US4956427A

  • Process for preparing polyolefins

    US9303095B2

  • Method for preparing oil-based dispersion

    CN109011718A

Cited By

  • Stabilizer composition and preparation method thereof

    CN121064369A

  • A stabilizer composition and its preparation method

    CN121064369B